Electronic Loyalty In Social Commerce: Scale Development and Validation - Bui Thanh Khoa; Ha Minh Nguyen (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Loyalty is an important key performance indicator to assess a business's success, especially in an online business environment with fierce competition. The explosion of social networking sites has created a new form of business: social commerce. Simultaneously, the scale of loyalty in online transactions has some limitations; hence, this research aims to develop and validate an electronic loyalty scale in the context of social commerce. The study used a mixed research method with two phases of a sequential exploratory strategy. Qualitative research generated the scale and was used in the initial filtering to develop an e-loyalty scale for social commerce. This study conducted two quantitative studies with 715 social commerce shoppers in five developed areas in Vietnam: Ho Chi Minh City, Ha Noi City, Hai Phong City, Da Nang City, and Binh Duong Province. Based on our research survey and literature review, the research results showed that electronic loyalty in social commerce is expressed in three dimensions: preference, interaction, and personal information’s disclosure. Then, the research proposed several relevant implications for other researchers and administrators of online businesses.